2023
DOI: 10.3389/fimmu.2023.1175384
|View full text |Cite
|
Sign up to set email alerts
|

Shared diagnostic genes and potential mechanism between PCOS and recurrent implantation failure revealed by integrated transcriptomic analysis and machine learning

Abstract: Polycystic ovary syndrome (PCOS) is a complex endocrine metabolic disorder that affects 5–10% of women of reproductive age. The endometrium of women with PCOS has altered immune cells resulting in chronic low-grade inflammation, which attribute to recurrent implantation failure (RIF). In this study, we obtained three PCOS and RIF datasets respectively from the Gene Expression Omnibus (GEO) database. By analyzing differentially expressed genes (DEGs) and module genes using weighted gene co-expression networks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Transcriptome overlap analysis is a genetic validation method for analyzing the relationship between two diseases. For example, based on three datasets of polycystic ovary syndrome and recurrent implantation failure, 12 disease overlapping genes were identified using weighted gene co expression networks, functional enrichment analysis, and three machine learning algorithms, which potential pathogenic associations and mechanisms between the two were explored [ 28 ]; The inflammatory immune pathway of calcified aortic valve disease (CAVD) related to chronic kidney disease (CKD) had been revealed, providing new insights for future serum based diagnosis and treatment interventions for CKD combined with CAVD [ 29 ]. In this study, 418 upregulated overlapping genes were identified using the GEO dataset of SLE and PBC, and their biological functions were found to be related to TNF signaling pathway and JAK-STAT signaling pathway, which was similar to previous reports [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome overlap analysis is a genetic validation method for analyzing the relationship between two diseases. For example, based on three datasets of polycystic ovary syndrome and recurrent implantation failure, 12 disease overlapping genes were identified using weighted gene co expression networks, functional enrichment analysis, and three machine learning algorithms, which potential pathogenic associations and mechanisms between the two were explored [ 28 ]; The inflammatory immune pathway of calcified aortic valve disease (CAVD) related to chronic kidney disease (CKD) had been revealed, providing new insights for future serum based diagnosis and treatment interventions for CKD combined with CAVD [ 29 ]. In this study, 418 upregulated overlapping genes were identified using the GEO dataset of SLE and PBC, and their biological functions were found to be related to TNF signaling pathway and JAK-STAT signaling pathway, which was similar to previous reports [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The essence of Gene Significance (GS) is the correlation between the genes within the module where it is located and the phenotype (our phenotype was selected as whether or not we had PD) [48]. Reviewing a large amount of literature, we found that, generally, a GS threshold between 0.2 and 0.5 is reasonable [53][54][55][56][57][58][59][60]. At the same time, we wanted to include as many genes as possible to see the relationship with ferroptosis, so for the GS threshold, we chose 0.2.…”
Section: Plos Onementioning
confidence: 99%